Production and quality of Murdannia bracteata biomass as impact of magnesium foliar fertilizer - Rahmawati, Tenti; Abdullah, Luki; Prihantoro, Iwan (Indonesian Animal Sciences Society, 2015)
Murdannia bracteata is one of potential forages for ruminant that has not been studied yet. This forage contents high mineral and it can be as fungtional feed. The aim of this study was to evaluate the growth and productivity, chlorophyll and minerals content of Murdannia bracteata caused by magnesium foliar application. The experiment was arranged in randomized complete design with five treatments and 4 replications. The application of magnesium level was arranged into: 0 ppm, 2000 ppm, 4000 ppm, 8000 ppm, and 12000 ppm. The study was conducted in a greenhouse, field laboratory of Agrostology, Faculty of Animal Science, Bogor Agricultural University. The result showed that growth, productivity, and chlorophyll content were not significantly (P>0.05) affected by increasing magnesium level. Increasing magnesium dossage resulted in decreasing calsium, potassium, and zink content (P<0,05), but not on phosphor and sodium (P>0,05). In conclusion, increasing magnesium dossage up to 12000 ppm did not significantly affect growth, productivity, and chlorophyll content. However, increasing magnesium level decreased calsium, potassium, and zink content. Key Words: Murdannia Bracteata, Magnesium, Productivity, Quality